Utilization of Technology as Promotion Media of Cultural Tourism in Central Java - veinta sonrizky mayo; Ridwan Sanjaya; Dwiyoga Widyarto (SISFORMA, 2016)
Tourism is one industry that is growing rapidly. Lots of models are offered and one of them is cultural tourism. One example of cultural tourism is a temple and a museum. In addition to the introduction through the temples and museums, the government's approach to conduct activities such as Dieng Culture Festival. Within these activities, the public can know more about the traditional ceremonial and moral values of Dieng. However, interest in the festival began to decrease each year. That's because the lack of a media campaign that resulted in people becoming not know and less concerned about the cultural tourism. If it continues, the cultural attractions such as museums will sink and disappear eroded by age. In this study, will discuss ways of promoting cultural tourism through the use of technology so that cultural tourism can be known internationally